Proceedings of the 2014 International Conference on Materials Science and Energy Engineering (CMSEE 2014) - Chung, Shyan-Lung; Li, Xiaolong (World Scientific Publishing, 2015)
"This proceedings collected together ninety-seven selected articles on recent research works and innovations in material science and energy engineering, presented at the 2014 International Conference on Materials Science and Energy Engineering (CMSEE 2014), held in Sanya, Hainan, China during December 12-14, 2014. CMSEE2014 covers a wide range of fundamental studies, technical innovations and industrial applications in material science and energy engineering, and were attended by 130 participants from different countries and regions in the world including China, Canada, Japan, Korea, Taiwan, Turkey, Egypt and Russia, to exchange notes on latest research, and synergic in future scientific collaborations. All papers submitted were subjected to a rigorous peer-review process by at least two independent reviewers to ensure that articles selected are of highest standard and are relevance to the aims and scope of CMSEE 2014"--